1997
DOI: 10.1164/ajrccm.156.4.96-08056
|View full text |Cite
|
Sign up to set email alerts
|

Increased Carbon Monoxide in Exhaled Air of Asthmatic Patients

Abstract: Exhaled carbon monoxide (CO) concentrations were measured on a CO monitor by vital capacity maneuvers in asthmatic patients receiving or not receiving inhaled corticosteroids and in nonsmoking and smoking healthy control subjects. CO was detectable and measured reproducibly in the exhaled air of all subjects. The exhaled CO concentrations were higher in asthmatic patients not receiving inhaled corticosteroids (5.6+/-0.6 ppm, p < 0.001) and similar in asthmatic patients receiving inhaled corticosteroids (1.7+/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
200
4
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(218 citation statements)
references
References 20 publications
7
200
4
7
Order By: Relevance
“…Uausuf et al [26] found eCO levels significantly higher (2.17±0.21) in children with persistent asthma compared to those with sporadic episodic asthma (1.39±0.18) and healthy children (1.01±0.12 ppm). As shown by Zayasu et al [27] asthmatic adults had eCO concentrations still higher (5.6±0.6 ppm) compared to nonsmoking healthy control subjects (1.5±0.1 ppm). However, non-asthmatic subjects with the symptoms of upper respiratory tract infections also presented eCO levels significantly elevated during the acute phase of the infection compared to recovery values (5.6±0.4 ppm vs. 1.0±0.1 ppm), which were similar result from oxidative stress experienced in the fetal period, and that HO activity in body tissues may be programmed in the fetal period by the exposure to fine particulate matter.…”
Section: Discussionmentioning
confidence: 72%
“…Uausuf et al [26] found eCO levels significantly higher (2.17±0.21) in children with persistent asthma compared to those with sporadic episodic asthma (1.39±0.18) and healthy children (1.01±0.12 ppm). As shown by Zayasu et al [27] asthmatic adults had eCO concentrations still higher (5.6±0.6 ppm) compared to nonsmoking healthy control subjects (1.5±0.1 ppm). However, non-asthmatic subjects with the symptoms of upper respiratory tract infections also presented eCO levels significantly elevated during the acute phase of the infection compared to recovery values (5.6±0.4 ppm vs. 1.0±0.1 ppm), which were similar result from oxidative stress experienced in the fetal period, and that HO activity in body tissues may be programmed in the fetal period by the exposure to fine particulate matter.…”
Section: Discussionmentioning
confidence: 72%
“…In two studies conducted by a Japanese group, the exhaled CO level was found to be higher in patients with asthma than in healthy individuals (2,3). In a meta-analysis that also referred to two studies conducted in Turkey (23,24), it was reported that the exhaled CO level was found to be higher in asthma patients who did not smoke than in those without asthma, and the CO level displayed a correlation with the severity of asthma (4).…”
Section: Discussionmentioning
confidence: 99%
“…CO is absorbed through smoking or can be produced endogenously in alveolar macrophages, endothelial cells, and other lung cells as a product of local inflammation and oxidative stress in individuals with airway diseases (1). In many studies, it was revealed that the end-expiratory CO (exhaled CO) level was higher in patients with severe asthma and lower in asthma patients receiving inhaled steroid therapy than in those not having therapy (2)(3)(4). Therefore, the exhaled CO level has recently begun to be used as an inflammatory biomarker in airway diseases such as asthma, chronic obstructive pulmonary disease (COPD), cystic fibrosis, and bronchiectasis (1,5).…”
Section: Introductionmentioning
confidence: 99%
“…Exhaled breath contains both gases, and aerosol droplets, however, the main focus of breath analysis thus far, has been on gas detection, which can contain: inorganic gases, i.e. NO [7] CO [8]; hydrocarbons, i.e. isoprene [9] ethane or pentane [10]; and volatile and non-volatile substances, such as isoprostane, cytokines, leukotrienes [11], proteins, nucleic acids, or polypeptides [12,13], bacteria or viruses.…”
Section: Introductionmentioning
confidence: 99%